Assessment of endothelial dysfunction in patients with impaired glucose tolerance during a cold pressor test. (November 2013) - Smirnova, Elena; Podtaev, Sergey; Mizeva, Irina; Loran, Evgenia
The objective of this study is to explore changes in microvascular tone during a contralateral cold pressor test and to compare the results obtained in healthy subjects and in patients with impaired glucose tolerance (IGT) and type 2 diabetes. Low-amplitude fluctuations of skin temperature in the appropriate frequency ranges were used as a characteristic for the mechanism for vascular tone regulation. In total, 13 adults with type 2 diabetes aged 40–67 years and 18 adults with IGT aged 31–60 years participated in this pilot study. The control group included 12 healthy men and women aged 39–60 years. The response to the cold pressor test in patients with type 2 diabetes and with IGT differs essentially from that of healthy subjects in the endothelial frequency range. Endothelial dysfunction occurs in the preclinical stage of diabetes and manifests, in particular, as a disturbance of the endothelial part of vascular tone regulation.